Boron diffusion in nanocrystalline 3C-SiC - Schnabel, M; Weiss, C; Canino, M; Rachow, T; Loeper, P; Summonte, C; Mirabella, S; Janz, S; Wilshaw, P (American Institute of Physics Inc., 2014)
The diffusion of boron in nanocrystalline silicon carbide (nc-SiC) films with a grain size of 4-7 nm is studied using a poly-Si boron source. Diffusion is found to be much faster than in monocrystalline SiC as it takes place within the grain boundary (GB) network. Drive-in temperatures of 900-1000 °C are suitable for creating shallow boron profiles up to 100 nm deep, while 1100 °C is sufficient to flood the 200 nm thick films with boron. From the resulting plateau at 1100 °C a boron segregation coefficient of 28 between nc-SiC and the Si substrate, as well as a GB boron solubility limit of 0.2 nm-2 is determined. GB diffusion in the bulk of the films is Fickian and thermally activated with DGB(T)=(3.1-5.6)×107exp(-5.03±0.16- eV/kBT) cm2s-1. The activation energy is interpreted in terms of a trapping mechanism at dangling bonds. Higher boron concentrations are present at the nc-SiC surface and are attributed to immobilized boron. © 2014 AIP Publishing LLC.